The assessment of writing within the CEFR scale : A Malaysian context - Engku Ibrahim, Engku Haliza; Sarudin, Isarji; Othman, Khairiah; Abdul Malik, Faridah; Muhamad, Ainon Jariah (American Scientific Publishers, 2017)
The Common European Framework of Reference for Languages: Learning, teaching, assessment (CEFR) by the Council of Europe, published in 2001, has stirred a lot of interest of education ministries and boards of education worldwide. One of the strengths of this framework is that it provides “a common basis for the elaboration of language syllabuses, curriculum guidelines, examinations, textbooks, etc. across Europe.”1 Within the Malaysian context, there is also a considerable interest on the part of the Malaysian Ministry of Education in moving towards using the CEFR scales in an attempt to provide a framework of reference for the description of competencies in the English language curriculum across the education levels, starting from kindergarten right up to tertiary level. This study presents a research that attempts to align the in-house English Proficiency Test (EPT) of the International Islamic University Malaysia (IIUM) to that of the CEFR scales. The focus of this exploratory study is on the assessment of the writing component where 143 writing scripts were graded according to the CEFR scales. The findings of this study indicate that the EPT Band correlate positively and hierarchically with the CEFR rating scale within an acceptable one band difference. These findings have implications for second language programmes in Malaysia and possibly other second language education programmes across the globe.